2005
DOI: 10.1002/bin.196
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of audio and visual stimulation on multiple forms of stereotypy

Abstract: Three experiments were conducted to evaluate the effects of audio and visual stimulation, alone or in combination, on the behavior of three children who displayed multiple forms of stereotypy (e.g., hand mouthing, body rocking). The results of experiment 1 showed that all three participants displayed different forms of stereotypy when audio and visual stimulation were provided versus when no stimulation was provided. The results of experiments 2 and 3 showed that the form of one participant's stereotypy, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 16 publications
6
31
0
Order By: Relevance
“…Thirteen data sets (from nine participants) that contained duration measures of behavior were selected from four published studies (Britton, Carr, Landaburu, & Romick, 2002;Falcomata, Roane, Hovanetz, & Kettering, 2004;Rapp, 2005;Rapp, Vollmer, Dozier, St. Peter, & Cotnoir, 2004). Three data sets from studies by Rapp and colleagues were initially scored using 10-s PIR (Rapp; Rapp et al).…”
Section: General Methods Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen data sets (from nine participants) that contained duration measures of behavior were selected from four published studies (Britton, Carr, Landaburu, & Romick, 2002;Falcomata, Roane, Hovanetz, & Kettering, 2004;Rapp, 2005;Rapp, Vollmer, Dozier, St. Peter, & Cotnoir, 2004). Three data sets from studies by Rapp and colleagues were initially scored using 10-s PIR (Rapp; Rapp et al).…”
Section: General Methods Proceduresmentioning
confidence: 99%
“…Because a number of recent studies have shown that duration-based events may covary (e.g., Lerman, Kelley, Vorndan, & Van Camp, 2003;Rapp, 2005;Rapp et al, 2004), the purpose of this experiment was to compare data paths generated with interval methods to data paths produced with CDR for the same events. For example, data collected with CDR may show that behavior A occurs for a higher percentage of time than behavior B during every session.…”
Section: Experiments 2: Evaluating Behavior-behavior Relationsmentioning
confidence: 99%
“…Rapp and colleagues (Rapp, 2004(Rapp, , 2005Rapp, Vollmer, St. Peter, Dozier, & Cotnoir, 2004) have conducted a series of experiments showing how response restriction may produce response reallocation towards other forms of stereotypy, but the studies did not focus on changes in appropriate behavior (e.g., toy play). First, researchers have published a restricted number of studies examining the collateral effects of interventions designed to reduce engagement in vocal stereotypy.…”
mentioning
confidence: 99%
“…The MO had mixed results on the participant's problem behavior in only two studies (Lanovaz, Fletcher, & Rapp, 2009;Rapp, 2005). The findings in Table 3 suggest that MOs' effects vary depending on the function of the problem behavior.…”
Section: Establishing or Abolishing Operationmentioning
confidence: 93%